2015
DOI: 10.1038/jid.2014.465
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Mortality of Neurofibromatosis: A Total Population Study in Finland

Abstract: was randomly selected from the background population, and there was virtually no loss to follow-up because of the precise linkage between the study cohort and various Danish health registries.In conclusion, the results of this large population-based cohort study showed no convincing association between obesity and risk for MM, whereas inverse associations were found between various anthropometric measures and risk for BCC in both genders and for SCC among women only. Additional studies with more accurate data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
191
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 227 publications
(200 citation statements)
references
References 14 publications
4
191
0
5
Order By: Relevance
“…At least 50% of cases present as de novo mutations of the gene and appear as isolated cases. NF1 has a birth incidence of one in 1,900 to 2,800 (20,21) and a diagnostic prevalence of one in 4,150 to 4,950 (20,21). The prevalence is lower than birth incidence due to undiagnosed cases in populations and an earlier mean age at death.…”
Section: Genetics and Epidemiologymentioning
confidence: 99%
“…At least 50% of cases present as de novo mutations of the gene and appear as isolated cases. NF1 has a birth incidence of one in 1,900 to 2,800 (20,21) and a diagnostic prevalence of one in 4,150 to 4,950 (20,21). The prevalence is lower than birth incidence due to undiagnosed cases in populations and an earlier mean age at death.…”
Section: Genetics and Epidemiologymentioning
confidence: 99%
“…Although estimates vary, it was recently suggested that the birth incidence may be as high as 1 in 2000 (1). NF1 is associated with several clinical manifestations, including benign and malignant tumors (27), cognitive delays, behavioral issues (810), autism (11, 12), and cardiovascular disease and abnormalities (13, 14).…”
mentioning
confidence: 99%
“…It has four main diagnostic signs which are visible in the skin, such as cafe´-au-lait spots, dermal neurofibromas, plexiform neurofibromas and axillary freckles. Among them, the first two are most common [2] . (Table 1) [9][10][11][12][13][14][15][16] .…”
Section: Discussionmentioning
confidence: 99%
“…The main clinical characteristics of the disease are cafe´-au-lait spots in the skin and dermal neurofibromas [2] .This multisystem disorder caused by a mutation in the NF 1 gene which has been identified on chromosome 17q11.2 [1] . The NF1 gene is a tumor suppressor, so the mutation of this gene results in loss of the corresponding protein function and the consequent development of benign or malignant tumors [3] .…”
Section: Introductionmentioning
confidence: 99%